Salivary Gland Extract of Kissing Bug, Triatoma lecticularia, Reduces the Severity of Intestinal Inflammation through the Modulation of the Local IL-6/IL-10 Axis - Sales-Campos, Helioswilton; da Silva Catarino, Jonatas; Roza, Guilherme Augusto; Obata Trevisan, Rafael; Menezes Silva, Luisa; Reis Machado, Juliana; da Silva, Marcos Vinícius; Andrade-Silva, Leonardo Euripedes; Rodrigues-Júnior, Virmondes; Freire de Oliveira, Carlo José (Mediators of Inflammation, 2018)
Triatomines are known for their role as vectors of the causative agent of Chagas disease. The occurrence of an arsenal of molecules in their saliva is able to suppress vertebrate immune responses. Thus, it is reasonable to assume that the presence of molecules with therapeutic potential in their saliva is able to constrain inflammation in immune-mediated diseases. Thus, mice were exposed to dextran sulfate sodium (DSS) in drinking water uninterruptedly during 6 consecutive days and treated with T. lecticularia salivary gland extract (SGE) (3, 10, or 30 μg) or vehicle (saline) (n=6/group). At the highest dose (30 μg), an improvement in clinical outcome and macroscopic aspects of the intestine were observed. This observation was followed by amelioration in histopathological aspects in the colon especially when the doses of 10 and 30 μg were used. Regardless of the concentration used, treatment with T. lecticularia SGE significantly reduced the levels of the inflammatory cytokine IL-6 in the intestine. The production of the anti-inflammatory cytokine IL-10 was positively impacted by the concentrations of 3 and 30 μg. Our results suggest that the presence of molecules in the T. lecticularia SGE is able to attenuate clinical outcome and colon shortening and improve intestinal architecture besides reducing the production of IL-6 and inducing a local production of IL-10 in the intestine.